Inorganic fine particle dispersion slurry composition and method for producing inorganic fine particle dispersion sheet using the same
By using a combination of (meth)acrylic resin with specific block segments and perovskite structure inorganic particles, the problem of difficulty in maintaining the crystal structure under low temperature conditions in the prior art is solved, and low temperature degreasing and performance inhibition are achieved , improves printing and moldability.
Patent Information
- Application Number
- CN202211018736.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2021-09-08
- Filing Date
- 2022-08-24
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2042-08-24
AI Technical Summary
In the prior art, when preparing perovskite-type inorganic materials, it is difficult to maintain an ideal crystal structure under low temperature conditions, and the high decomposition temperature requirements of the adhesive lead to high temperature treatment, resulting in reduced performance.
(meth)acrylic resin with polypropylene glycol block segment or polytetramethylene ether glycol block segment is used as the binder, and inorganic particles with perovskite structure are maintained through the firing process. Excellent properties of particles.
Degreasing under low temperature conditions below Curie point is achieved, and deterioration of magnetic and piezoelectric properties of perovskite-type inorganic materials is suppressed, while improving printing and moldability.
Smart Images

Figure BDA0003813289090000221 
Figure BDA0003813289090000241
Abstract
Description
Technical Field
[0001] The present invention relates to an inorganic fine particle dispersion slurry composition and a method for producing an inorganic fine particle dispersion sheet using the same. Background Art
[0002] Compositions in which inorganic fine particles such as ceramic powders and glass particles are dispersed in a binder resin are used in the production of various electronic components. Among them, inorganic fine particles having a perovskite structure having excellent properties are used as functional inorganic materials in various fields.
[0003] As functional inorganic materials having a perovskite structure, there are neodymium magnets (Nd 2 Fe 14 B), PZT piezoelectric element (Pb(Zr,Ti)O 3 ), all-solid-state battery LLTO electrolyte (Li 0.33 La 0.56 TiO 3 ) etc. It is known that these functional inorganic materials are composed of three or more element units, and the three elements form a crystal structure called perovskite to exert various properties.
[0004] For example, for neodymium magnets, which are known as the strongest magnets, an alloy containing neodymium, iron, and boron is crushed into a size of several microns using a jet mill, and then kneaded with a binder and a solvent to form an inorganic fine particle dispersion slurry. After that, after being formed by coating, pouring into a mold and pressing in a magnetic field, etc., it is degreased and sintered in a sintering furnace. Generally, a cellulose resin or the like is used as a binder.
[0005] For example, Patent Document 1 studies the following: forming a thin film by sputtering a magnet component while heating a support to 250 to 400° C. near the Curie temperature. Patent Document 2 studies the following: using a block polymer of polystyrene-b-poly(4-vinylpyridine) as a binder, and using the phase separation structure formed by these polymers to sinter an inorganic group into an ideal structure.
[0006] Prior art literature
[0007] Patent Literature
[0008] Patent Document 1: International Publication No. 2021 / 065254
[0009] Patent Document 2: Japanese Patent No. 6770704 Summary of the invention
[0010] Problems to be solved by the invention
[0011] According to the method described in Patent Document 1, since no binder is used in film formation, there is no concern about thermal degradation associated with degreasing, but it is difficult to obtain an ideal perovskite crystal structure. In addition, in the method described in Patent Document 2, the decomposition temperature of polystyrene-b-poly(4-vinylpyridine) used as a binder is as high as that of cellulose, and for degreasing, a high-temperature treatment at 700°C for 6 hours is required, which requires treatment at a temperature higher than the Curie temperature, resulting in a problem of reduced performance.
[0012] The object of the present invention is to provide an inorganic particle dispersion slurry composition which has excellent low-temperature decomposition properties, can perform degreasing of perovskite-type inorganic materials below the Curie point, can suppress the degradation of magnetic force and piezoelectric properties of perovskite-type inorganic materials, and has excellent printability. In addition, the object of the present invention is to provide a method for producing an inorganic particle dispersion sheet using the inorganic particle dispersion slurry composition.
[0013] Means for solving problems
[0014] The present invention relates to an inorganic fine particle dispersion slurry composition, which contains a (meth)acrylic resin (A), inorganic fine particles (B) and a solvent (C), wherein the inorganic fine particles (B) are a three-element inorganic material or a four-element inorganic material having a perovskite structure, and the (meth)acrylic resin (A) has at least one of a polypropylene glycol block segment and a polytetramethylene ether glycol block segment.
[0015] Hereinafter, the present invention will be described in detail.
[0016] The present inventors have found that by using a (meth) acrylic resin (A) having a polypropylene glycol block segment or a polytetramethylene ether glycol block segment as a binder for perovskite-type inorganic fine particles (B), sintering at 300°C, which is close to the Curie temperature of the inorganic fine particles, is possible. In addition, the inventors have found that a molded product can be produced while maintaining the excellent properties of the perovskite-type inorganic fine particles (B), thereby completing the present invention.
[0017] <(Meth)acrylic resin (A)>
[0018] The inorganic fine particle-dispersed slurry composition of the present invention contains a (meth)acrylic resin (A).
[0019] The (meth)acrylic resin (A) has at least one of a polypropylene glycol block segment and a polytetramethylene ether glycol block segment.
[0020] By having such a structure, the inorganic fine particles maintain an ideal crystal structure even after firing, and can maintain the excellent characteristics of the inorganic fine particles having a perovskite structure.
[0021] The inorganic fine particle-dispersed slurry composition of the present invention preferably has the above-mentioned polypropylene glycol block segment or the above-mentioned polytetramethylene ether glycol block segment in the graft chain.
[0022] When the (meth)acrylic resin (A) has a comb-shaped polymer structure having graft chains, it is easy to form an intramolecular phase separation structure, and the inorganic fine particles are more likely to maintain a perovskite structure after calcination.
[0023] When the average length of the main chain of the (meth)acrylic resin (A) is 100, the average length of the polypropylene glycol block segment and the polytetramethylene ether glycol block segment in the (meth)acrylic resin (A) is preferably 0.1 or more and preferably 5.0 or less.
[0024] If the average length is 0.1 or more, the block segments can be introduced to fully exert the property-maintaining effect of the inorganic particles having a perovskite structure. If the average length is 5.0 or less, the polymer chains are less likely to entangle with each other, and the printability of the inorganic particle dispersion slurry composition can be fully improved.
[0025] The average length is preferably 1.0 or more, more preferably 2.0 or more, and is preferably 4.5 or less, more preferably 4.0 or less.
[0026] About the average length of the above-mentioned polypropylene glycol block segment and polytetramethylene ether glycol block segment, it is the value converted by the ratio of the molecular weight of the polypropylene glycol block segment and the polytetramethylene ether glycol block segment when the number average molecular weight (Mn) of the (meth) acrylic resin (A) is set to 100. It should be noted that in the determination of the number average molecular weight (Mn) of the (meth) acrylic resin based on polystyrene conversion described later, there is no influence caused by the molecular weight of the graft chain. Therefore, by the ratio between the Mn of the (meth) acrylic resin (A) and the molecular weight of the polypropylene glycol block segment and the polytetramethylene ether glycol block segment, the average length of the graft chain relative to the average length of the main chain can be obtained.
[0027] The above average length can be measured, for example, by comparing the GPC analysis before and after saponification.
[0028] The composition ratio of the polypropylene glycol block segment and the polytetramethylene ether glycol block segment in the (meth)acrylic resin (A) is preferably 5 wt % or more, more preferably 7 wt % or more, and is preferably 20 wt % or less, more preferably 15 wt % or less.
[0029] If the composition ratio is 5 wt % or more, the block segments are introduced to fully exert the property-maintaining effect of the inorganic particles having the perovskite structure. If the composition ratio is 20 wt % or less, the island component does not become excessive in the intramolecular phase separation structure, and the inorganic particles are more likely to maintain the perovskite structure after calcination.
[0030] In addition, the said composition ratio shows the weight ratio of only the graft chain part except the main chain part in (meth)acrylic resin (A).
[0031] The composition ratio can be measured, for example, by evaluating the dry weight before and after saponification or by comparing the (meth)acrylic resin by GPC analysis.
[0032] When the (meth)acrylic resin (A) has the polypropylene glycol block segment or the polytetramethylene ether glycol block segment in the graft chain, the content of the block segment as the graft chain in the (meth)acrylic resin (A) is preferably 5% by weight or more, more preferably 7% by weight or more, and is preferably 20% by weight or less, more preferably 15% by weight or less.
[0033] If the content of the block segment as the graft chain is 5% by weight or more, the block segment is introduced to fully exert the property-maintaining effect of the inorganic particles having the perovskite structure. If the content of the block segment as the graft chain is 20% by weight or less, the island component will not become too much in the intramolecular phase separation structure, and the inorganic particles will be easier to maintain the perovskite structure by calcination.
[0034] In addition, the said content shows the weight ratio of the structural unit which has the said graft chain in (meth)acrylic resin (A).
[0035] The content of the block segments as the graft chains can be obtained, for example, by saponifying the (meth)acrylic resin with an aqueous sodium hydroxide solution or the like to hydrolyze the ester chains, separating the oil droplets from the (meth)acrylic resin, measuring the weights of the dried oil droplets and the saponified (meth)acrylic resin (A) as a whole, and calculating the composition ratio of the block segments as the graft chains by the following formula.
[0036] Content of block segments as graft chains = (weight of dried oil droplet-like components / weight of saponified (meth)acrylic resin (A)) × 100
[0037] The (meth)acrylic resin (A) preferably has a segment derived from isobutyl methacrylate.
[0038] By having a segment derived from isobutyl methacrylate, the low-temperature decomposability of the (meth)acrylic resin (A) can be further improved.
[0039] The content of the segment derived from isobutyl methacrylate in the (meth)acrylic resin (A) is preferably 50% by weight or more and preferably 80% by weight or less.
[0040] When the content is 50% by weight or more, the low-temperature decomposability of the (meth)acrylic resin (A) can be further improved. When the content is 80% by weight or less, the block segments can be sufficiently introduced into the (meth)acrylic resin (A), and the effect of introducing the block segments can be fully exerted.
[0041] The content of the segment derived from isobutyl methacrylate in the (meth)acrylic resin (A) is more preferably 55% by weight or more, further preferably 60% by weight or more, and more preferably 75% by weight or less, further preferably 70% by weight or less.
[0042] By setting it as the said range, low-temperature decomposability and printability can be improved sufficiently, and it becomes easier for the inorganic fine particles to maintain the perovskite structure.
[0043] The content of the segment derived from isobutyl methacrylate in the (meth)acrylic resin (A) is preferably 50 mol% or more and preferably 80 mol% or less.
[0044] When the content is 50 mol% or more, the low-temperature decomposability of the (meth)acrylic resin (A) can be further improved. When the content is 80 mol% or less, the block segments can be sufficiently introduced into the (meth)acrylic resin (A), and the effect of introducing the block segments can be fully exerted.
[0045] The content of the segment derived from isobutyl methacrylate in the (meth)acrylic resin (A) is more preferably 55 mol% or more, further preferably 60 mol% or more, and more preferably 75 mol% or less, further preferably 70 mol% or less.
[0046] By setting it in the said range, low-temperature decomposability and printability can be improved sufficiently, and it becomes easier for the inorganic fine particles to maintain a perovskite structure.
[0047] The above content can be measured by, for example, thermal decomposition GC-MS.
[0048] The (meth)acrylic resin (A) may have other segments in addition to the polypropylene glycol block segment, the polytetramethylene ether glycol block segment, and the segment derived from isobutyl methacrylate.
[0049] Examples of the other segment include a segment derived from a (meth)acrylic acid ester having an ester substituent with 1 to 10 carbon atoms.
[0050] By containing the segment derived from the (meth)acrylate having 1 to 10 carbon atoms in the ester substituent, the glass transition temperature of the (meth)acrylic resin (A) can be increased and the brittleness can be improved.
[0051] Examples of the (meth)acrylate having an ester substituent with 1 to 10 carbon atoms include (meth)acrylic acid alkyl esters having a linear alkyl group with 1 to 10 carbon atoms, branched (meth)acrylates, and cyclic (meth)acrylates.
[0052] More specifically, methyl (meth)acrylate, ethyl (meth)acrylate, n-propyl (meth)acrylate, n-butyl (meth)acrylate, n-pentyl (meth)acrylate, n-hexyl (meth)acrylate, etc. are mentioned. Also, isopropyl (meth)acrylate, sec-butyl (meth)acrylate, tert-butyl (meth)acrylate, isopentyl (meth)acrylate, neopentyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, etc. are mentioned. In addition, cyclohexyl (meth)acrylate, etc. are mentioned.
[0053] Among them, methyl (meth)acrylate, ethyl (meth)acrylate, n-butyl (meth)acrylate, and 2-ethylhexyl (meth)acrylate are preferred, and methyl methacrylate, ethyl methacrylate, n-butyl methacrylate, and 2-ethylhexyl methacrylate are more preferred.
[0054] The content of the segment derived from the (meth)acrylic acid ester in which the carbon number of the ester substituent is 1 to 10 in the (meth)acrylic resin (A) is preferably 1% by weight or more, more preferably 10% by weight or more, and preferably 40% by weight or less, more preferably 30% by weight or less.
[0055] Moreover, as said other segment, besides this, (meth)acrylate which has a glycidyl group, (meth)acrylate which has a hydroxyl group or a carboxyl group, etc. are mentioned.
[0056] As said glycidyl group-containing (meth)acrylate, glycidyl (meth)acrylate, 4-hydroxybutyl acrylate glycidyl ether, 3, 4-epoxycyclohexylmethyl methacrylate, etc. are mentioned, for example.
[0057] Examples of the (meth)acrylate having a hydroxyl group or a carboxyl group include 2-hydroxyethyl (meth)acrylate, hydroxypropyl (meth)acrylate, hydroxybutyl (meth)acrylate, and (meth)acrylic acid.
[0058] The content of the other segments in the (meth)acrylic resin is preferably 1% by weight or more, more preferably 4% by weight or more, and is preferably 10% by weight or less, more preferably 7% by weight or less.
[0059] By setting it as the said range, the low-temperature decomposability of a (meth)acrylic resin (A) can be improved sufficiently, and the toughness of the obtained inorganic fine particle-dispersed sheet can be improved.
[0060] The weight average molecular weight (Mw) of the (meth)acrylic resin (A) is preferably 20,000 or more and preferably 100,000 or less.
[0061] When the Mw is 20,000 or more, the viscosity of the inorganic fine particle dispersion slurry composition does not become too low, and the dispersibility of the inorganic fine particles can be improved. When the Mw is 100,000 or less, the printability of the inorganic fine particle dispersion slurry composition can be improved.
[0062] The Mw is preferably 30,000 or more, more preferably 40,000 or more, and is preferably 80,000 or less, more preferably 70,000 or less.
[0063] The number average molecular weight (Mn) of the (meth)acrylic resin (A) is preferably 10,000 or more, more preferably 15,000 or more, and is preferably 40,000 or less, more preferably 35,000 or less.
[0064] The (meth)acrylic resin (A) preferably has a ratio (Mw / Mn) of the weight average molecular weight (Mw) to the number average molecular weight (Mn) of 1.5 or more and preferably 5 or less.
[0065] By setting the above range, the composition with low polymerization degree is appropriately contained, so that the viscosity of the inorganic microparticle dispersion slurry composition becomes an ideal range, which can improve productivity. In addition, the sheet strength of the obtained inorganic microparticle dispersion sheet can be appropriately made. In addition, the surface smoothness of the obtained ceramic green sheet can be fully improved.
[0066] The above-mentioned Mw / Mn is more preferably 2 or more, and more preferably 3 or less.
[0067] The weight average molecular weight (Mw) and the number average molecular weight (Mn) are average molecular weights calculated on the basis of polystyrene, and can be obtained by, for example, performing GPC measurement using a column LF-804 (manufactured by Showa Denko K.K.) as a column.
[0068] The glass transition temperature (Tg) of the (meth)acrylic resin (A) is preferably 30° C. or higher, more preferably 40° C. or higher, and is preferably 80° C. or lower, more preferably 70° C. or lower.
[0069] In addition, the said glass transition temperature (Tg) can be measured using a differential scanning calorimeter (DSC) etc., for example.
[0070] The content of the (meth)acrylic resin (A) in the inorganic fine particle-dispersed slurry composition of the present invention is not particularly limited, but is preferably 5% by weight or more and preferably 30% by weight or less.
[0071] By setting the content of the (meth)acrylic resin within the above range, it is possible to obtain an inorganic fine particle-dispersed slurry composition that can be degreased even when firing is performed at a low temperature.
[0072] The content of the (meth)acrylic resin is more preferably 6% by weight or more, and more preferably 12% by weight or less.
[0073] The method for producing the (meth)acrylic resin (A) is not particularly limited, and for example, the following method can be cited: first, an organic solvent is added to a raw monomer mixture containing (meth)acrylic acid, glycidyl (meth)acrylate, etc. to prepare a monomer mixture, and further, a polymerization initiator is added to the obtained monomer mixture to polymerize to produce a raw (meth)acrylic resin. Next, a compound having a propylene glycol chain and a compound having a polytetramethylene ether glycol chain are reacted with the raw (meth)acrylic resin to introduce a propylene glycol block segment and a polytetramethylene ether glycol block segment to produce the (meth)acrylic resin (A).
[0074] In addition, the following method can be mentioned: polypropylene glycol, polytetramethylene ether glycol are reacted with maleic anhydride, 2-methacryloyloxyethyl isocyanate, etc. to prepare a monomer having a polypropylene glycol block segment and a polytetramethylene ether glycol block segment. Next, the obtained monomer is mixed with (meth)acrylate, etc. to prepare a raw monomer mixture, and further, an organic solvent, etc. are added to prepare a monomer mixed solution, and further, a polymerization initiator is added to the obtained monomer mixed solution, and polymerization is carried out to prepare a (meth)acrylic resin (A).
[0075] In addition, there is a method in which a (meth)acrylic acid ester such as (meth)acrylic acid or glycidyl (meth)acrylate is mixed with polypropylene glycol or polytetramethylene ether glycol and reacted to produce a (meth)acrylic resin (A).
[0076] The polymerization method is not particularly limited, and examples thereof include emulsion polymerization, suspension polymerization, bulk polymerization, interfacial polymerization, solution polymerization, etc. Among them, solution polymerization is preferred.
[0077] Examples of the polymerization initiator include dilauroyl peroxide, p-menthane hydroperoxide, diisopropylbenzene hydroperoxide, 1,1,3,3-tetramethylbutyl hydroperoxide, cumene hydroperoxide, tert-butyl hydroperoxide, cyclohexanone peroxide, and disuccinic acid peroxide.
[0078] Examples of commercial products thereof include PERMENTA H, PERCUMYL P, PEROCTA H, PERCUMYL H-80, PEROYL 355, PERBUTYL H-69, PERHEXA H, PEROYL SA, and PEROYL L (all manufactured by NOF Corporation), Trigonox 27, and Trigonox 421 (all manufactured by Nouryon).
[0079] <Inorganic fine particles (B)>
[0080] The inorganic fine particle-dispersed slurry composition of the present invention contains inorganic fine particles (B).
[0081] The inorganic fine particles (B) are three-element or four-element inorganic materials having a perovskite structure.
[0082] The so-called perovskite structure is a perovskite CaTiO 3 Inorganic particles of the same crystal structure and consisting essentially of ABX 3 The three constituent elements of the cubic crystal are arranged at the body center of the cubic crystal, the B atoms are arranged at each vertex, and the X atoms are arranged at each face center of the cubic crystal. 3 ) and lead titanate (PbTiO 3 ) mixed crystal, namely PZT(Pb(ZrTi)O 3 ) is a 4-element system.
[0083] As Nd 2 Fe 14 B (Curie point temperature 312°C), PbZrTiO 3 (Curie point temperature 350°C) As shown in FIG. 1 , most perovskite-type inorganic fine particles have a Curie point of about 300°C, and by sintering at a temperature lower than the Curie point, that is, 300°C, an inorganic material product can be manufactured while maintaining the original characteristics.
[0084] The inorganic fine particles (B) having a perovskite structure are combined with the (meth) acrylic resin (A) to prepare an inorganic fine particle dispersion slurry composition, which is then calcined to prepare an inorganic fine particle dispersion molded body, thereby obtaining a molded body without impairing the excellent properties of the inorganic fine particles having a perovskite structure.
[0085] The inorganic fine particles (B) having a perovskite structure are not particularly limited, and examples thereof include: Sm 2 Fe 17 N 3 、Nd 2 Fe 14 B, MnAlC, L 10 FeNi、La 2 / 3-x Li 3x TiO 3 ,La (1-x) / 3 Li x NbO 3 、LaGaO 3 、LaScO 3 、CaZrO 3 , (La 0.875 Sr 0.125 )MnO 3 、Pb(Zr,Ti)O 3 、SrBi 2 Ta 2 O 9 、BiFeO 3 , KNbO 3 、PbVO 3 、BiCo 3 、Bi(Zn 1 / 2 Ti 1 / 2 ) 3 Among them, Nd is preferred 2 Fe 14 B. Pb(Zr,Ti)O 3 .
[0086] The content of the inorganic fine particles (B) in the inorganic fine particle-dispersed slurry composition of the present invention is preferably 40% by weight or more and preferably 90% by weight or less.
[0087] When the content is 40% by weight or more, the density of the inorganic fine particles (B) in the molded body can be sufficiently increased. When the content is 90% by weight or less, the dispersibility of the inorganic fine particles (B) can be sufficiently increased to improve moldability.
[0088] The content of the inorganic fine particles (B) is preferably 50% by weight or more and preferably 80% by weight or less.
[0089] When the content is within the above range, the coating properties and printability of the inorganic fine particle dispersed slurry composition can be sufficiently improved, and a dense molded body after firing can be obtained.
[0090] The average particle size of the inorganic fine particles (B) is preferably 0.1 μm or more, more preferably 0.5 μm or more, and is preferably 100 μm or less, more preferably 50 μm or less.
[0091] By setting it as the said range, the specific surface area of an inorganic fine particle (B) will not become too large, the binder residue can be reduced, and a dense molded body can be obtained by sintering.
[0092] The average particle size can be measured by, for example, observation using a SEM.
[0093] <Solvent (C)>
[0094] The inorganic fine particle dispersion slurry composition of the present invention contains an organic solvent.
[0095] The organic solvent is not particularly limited, but is preferably an organic solvent that is excellent in coating properties, drying properties, dispersibility of inorganic powders, etc. when producing an inorganic fine particle dispersed sheet.
[0096] For example, toluene, ethyl acetate, butyl acetate, hexyl acetate, isopropyl alcohol, methyl isobutyl ketone, methyl ethyl ketone, methyl isobutyl ketone, ethylene glycol ethyl ether, ethylene glycol monobutyl ether, ethylene glycol monoethyl ether acetate, diethylene glycol monoethyl ether, diethylene glycol monomethyl ether, diethylene glycol monoisobutyl ether, trimethylpentanediol monoisobutyrate, butyl carbitol, butyl carbitol acetate, terpineol, terpineol acetate, dihydroterpineol, dihydroterpineol acetate, TEXANOL, isophorone, butyl lactate, dioctyl phthalate, dioctyl adipate, benzyl alcohol, phenylpropylene glycol, cresol, ethyl carbitol acetate, and the like can be mentioned. Among them, butyl acetate, hexyl acetate, ethyl carbitol acetate, terpineol, terpineol acetate, dihydroterpineol, dihydroterpineol acetate, diethylene glycol monoethyl ether, diethylene glycol monomethyl ether, diethylene glycol monoisobutyl ether, butyl carbitol, butyl carbitol acetate, and TEXANOL are preferred. In addition, butyl acetate, hexyl acetate, terpineol, and ethyl carbitol acetate are more preferred. It should be noted that such organic solvents can be used alone or in combination of two or more.
[0097] The boiling point of the organic solvent is preferably 90 to 230° C. If the boiling point is 90° C. or higher, evaporation does not become too rapid, and an inorganic fine particle dispersion slurry composition with excellent handling properties can be obtained. If the boiling point is 230° C. or lower, the inorganic fine particle dispersion slurry composition is not easy to dry, and excellent printability can be obtained.
[0098] The content of the organic solvent in the inorganic fine particle dispersion slurry composition of the present invention is not particularly limited, but the preferred lower limit is 10 wt % and the preferred upper limit is 60 wt %. By setting the content within the above range, the coating properties and the dispersibility of the inorganic fine particles can be improved.
[0099] <Other>
[0100] The inorganic fine particle-dispersed slurry composition of the present invention may further contain a plasticizer.
[0101] Examples of the plasticizer include dibutoxyethyl adipate, dibutoxyethoxyethyl adipate, triethylene glycol dibutyl ether, triethylene glycol bis(2-ethylhexanoate), triethylene glycol dicaproate, triethyl acetyl citrate, tributyl acetyl citrate, diethyl acetyl citrate, dibutyl acetyl citrate, dibutyl sebacate, glycerol triacetate, diethyl acetoxymalonate, and diethyl ethoxymalonate.
[0102] By using these plasticizers, the amount of plasticizer added can be reduced compared to the case of using ordinary plasticizers (when about 30% by weight is added to the binder, it can be reduced to 25% by weight or less, and further reduced to 20% by weight or less).
[0103] Among them, it is preferred to use a non-aromatic plasticizer that does not contain an aromatic ring such as a benzene ring in the structure, and more preferably contains a component derived from adipic acid, triethylene glycol, citric acid or succinic acid. It should be noted that plasticizers with aromatic rings are not preferred because they easily become soot when burned.
[0104] The plasticizer is preferably a plasticizer having an alkyl group having 2 or more carbon atoms, such as an ethyl group or a butyl group, and more preferably a plasticizer having an alkyl group having 4 or more carbon atoms.
[0105] The plasticizer contains an alkyl group having at least 2 carbon atoms, thereby suppressing the absorption of water into the plasticizer and preventing the resulting inorganic fine particle dispersed sheet from having defects such as voids and swelling. In particular, the alkyl group of the plasticizer is preferably located at the molecular terminal.
[0106] The plasticizer preferably has a functional group having 2 carbon atoms, such as an ethyl group, a functional group having 4 carbon atoms, such as a butyl group, or a butoxyethyl group. The functional group is preferably present at a molecular terminal.
[0107] Plasticizers having a functional group with a carbon number of 2, such as an ethyl group, at the molecular end have good compatibility with the segment derived from ethyl methacrylate, and plasticizers having a functional group with a carbon number of 4, such as a butyl group, at the molecular end have good compatibility with the segment derived from butyl methacrylate. Plasticizers having a functional group with a carbon number of 2 or 4 have good compatibility with the (meth) acrylic resin involved in the present invention, and can preferably improve the brittleness of the resin. In addition, as for butoxyethyl, it has good compatibility with the composition of the segment derived from ethyl methacrylate and the segment derived from butyl methacrylate, and can be preferably used.
[0108] In the above plasticizer, the carbon:oxygen ratio is preferably 5:1 to 3:1.
[0109] By setting the carbon:oxygen ratio within the above range, the combustibility of the plasticizer can be improved to prevent the generation of residual carbon, and the compatibility with the (meth)acrylic resin can be improved, so that even a small amount of the plasticizer can exert a plasticizing effect.
[0110] In addition, a high boiling point organic solvent having a propylene glycol skeleton or a trimethylene glycol skeleton can be preferably used if it also contains an alkyl group having 4 or more carbon atoms and has a carbon:oxygen ratio of 5:1 to 3:1.
[0111] The boiling point of the plasticizer is preferably 240° C. or higher and lower than 390° C. By setting the boiling point to 240° C. or higher, the plasticizer is easily evaporated during the drying process and can be prevented from remaining in the molded body. In addition, by setting the boiling point to lower than 390° C., the generation of residual carbon can be prevented. It should be noted that the boiling point is the boiling point at normal pressure.
[0112] The content of the plasticizer in the inorganic fine particle dispersion slurry composition of the present invention is not particularly limited, but the preferred lower limit is 0.1 wt % and the preferred upper limit is 3.0 wt %. By setting the content within the above range, the burning residue of the plasticizer can be reduced.
[0113] The inorganic fine particle dispersion slurry composition of the present invention may further contain additives such as a surfactant.
[0114] The surfactant is not particularly limited, and examples thereof include cationic surfactants, anionic surfactants, and nonionic surfactants.
[0115] The above-mentioned nonionic surfactant is not particularly limited, and is preferably a nonionic surfactant having an HLB value of 10 or more and 20 or less. Here, the so-called HLB value is a value used as an index of the hydrophilicity and lipophilicity of the surfactant. Several calculation methods have been proposed, such as the following definitions: for ester-based surfactants, the saponification value is set to S, the acid value of the fatty acid constituting the surfactant is set to A, and the HLB value is set to 20 (1-S / A). Specifically, it is preferably a nonionic surfactant having polyoxyethylene obtained by adding an alkylene ether to a fatty chain, and specifically, for example, polyoxyethylene lauryl ether, polyoxyethylene cetyl ether, etc. are preferably used. It should be noted that the above-mentioned nonionic surfactant has good thermal decomposition, but if it is added in large quantities, the thermal decomposition of the inorganic microparticle dispersion slurry composition is sometimes reduced, so the preferred upper limit of the content is 5% by weight.
[0116] The viscosity of the inorganic fine particle dispersion slurry composition of the present invention is not particularly limited, but when measured at 20° C. using a B-type viscometer with a probe rotation speed of 5 rpm, the preferred lower limit of the viscosity is 0.1 Pa·s, and the preferred upper limit is 100 Pa·s.
[0117] By setting the above viscosity to more than 0.1 Pa·s, the obtained inorganic fine particle dispersion sheet can maintain a predetermined shape after being coated by a die coating printing method, etc. In addition, by setting the above viscosity to less than 100 Pa·s, it is possible to prevent the mold coating marks (Japanese: Tuotou marks) from disappearing and other undesirable conditions, thereby achieving excellent printability.
[0118] The method for preparing the inorganic fine particle dispersion slurry composition of the present invention is not particularly limited, and a conventionally known stirring method can be cited. Specifically, for example, a method in which the (meth)acrylic resin (A), the inorganic fine particles (B), the solvent (C), and other components such as a plasticizer added as needed are stirred using a three-roll mill or the like.
[0119] The inorganic fine particle dispersion slurry composition of the present invention is applied and dried to form a sheet, and the obtained sheet is further fired at a temperature of 350° C. or lower, thereby producing an inorganic fine particle dispersion sheet.
[0120] A method for producing an inorganic fine particle dispersed sheet comprising the steps of applying and drying the inorganic fine particle dispersed slurry composition of the present invention to obtain a sheet, and calcining the sheet at 350° C. or lower is also one of the present invention.
[0121] The inorganic fine particle dispersed slurry composition of the present invention is applied to a support film subjected to a release treatment on one side, and the organic solvent is dried to form a sheet, thereby producing an inorganic fine particle dispersed sheet.
[0122] The thickness of the inorganic fine particle dispersed sheet of the present invention is preferably 1 to 20 μm.
[0123] The printing and molding method of the inorganic particle dispersion slurry composition of the present invention is not particularly limited, and a coil shape may be formed by alternately applying a U-shaped opening screen plate up and down, or directly printing on a substrate to form a laminate, or the substrate may be dip-coated in the inorganic particle dispersion slurry composition. By using a high boiling point organic solvent, molding can be performed using screen printing or the like.
[0124] Examples of the coating method include a method of uniformly forming a coating film of the inorganic fine particle dispersion slurry composition of the present invention on a support film by a coating method such as a roll coater, a die coater, an extrusion coater, or a curtain coater.
[0125] Examples of the drying method include heat drying, etc. The drying temperature is preferably 80 to 130°C.
[0126] The support film used when manufacturing the inorganic microparticle dispersion sheet of the present invention is preferably a resin film with heat resistance and solvent resistance and flexibility. By making the support film flexible, the inorganic microparticle dispersion slurry composition can be applied to the surface of the support film by a roll coater, a scraper coater, etc., and the obtained inorganic microparticle dispersion sheet can be formed into a film and stored and supplied in a state of being wound into a roll.
[0127] Examples of the resin forming the support film include polyethylene terephthalate, polyester, polyethylene, polypropylene, polystyrene, polyimide, polyvinyl alcohol, fluorine-containing resins such as polyvinyl chloride and polyvinyl fluoride, nylon, and cellulose.
[0128] The thickness of the support film is preferably, for example, 20 to 100 μm.
[0129] In addition, it is preferable to subject the surface of the support film to a release treatment, whereby the peeling operation of the support film can be easily performed in the transfer step.
[0130] In the calcining step, the heating temperature is preferably 350° C. or lower and 250° C. or higher.
[0131] For example, in the inorganic fine particle dispersion slurry composition of the present invention, Nd 2 Fe 14 When B is inorganic fine particles (B), the slurry is printed on a ferrite magnet substrate, dried, and subjected to magnetic pressing to be fired at about 300° C. while magnetically orienting the slurry. Thus, a neodymium magnet with reduced magnetic drop can be produced.
[0132] In addition, for example, in the inorganic fine particle dispersion slurry composition of the present invention, Li 0.33 La 0.56 TiO 3 (LLTO) as the inorganic fine particles (B) was used to prepare a slurry composition, which was solid-printed on the negative electrode Li foil and then dried. 0.33 La 0.56 TiO 3 By laminating positive electrode sheets of (LLTO), acetylene black as a conductive aid, and lithium niobium oxide as a positive electrode active material and sintering them at 300°C, a large-capacity all-solid-state battery can be manufactured.
[0133] When the sintering property of the inorganic fine particles (B) is insufficient when calcined at about 300° C., borosilicate, phosphate, etc. may be added as a sintering aid.
[0134] Furthermore, a multilayer ceramic capacitor can be produced by using the inorganic fine particle-dispersed slurry composition and the inorganic fine particle-dispersed sheet of the present invention for a dielectric green sheet or an electrode paste.
[0135] As a method for manufacturing the above-mentioned all-solid-state battery, there can be cited a manufacturing method having the following steps: a step of forming a slurry for an electrode active material layer containing an electrode active material and a binder for an electrode active material layer to produce an electrode active material sheet; a step of stacking the above-mentioned electrode active material sheet and the inorganic fine particle dispersion sheet of the present invention to produce a stacked body; and a step of sintering the above-mentioned stacked body.
[0136] The electrode active material is not particularly limited, and for example, the same material as the inorganic fine particles can be used.
[0137] The above-mentioned (meth)acrylic resin can be used as the binder for the electrode active material layer.
[0138] Examples of a method for laminating the electrode active material sheet and the inorganic fine particle dispersed sheet of the present invention include a method in which each sheet is formed and then subjected to thermocompression bonding or thermal lamination using heat pressing.
[0139] In the calcining step, the preferred lower limit of the heating temperature is 250°C, and the preferred upper limit is 350°C.
[0140] When the heating temperature is within the above range, the excellent properties of the inorganic fine particles (B) can be maintained.
[0141] Through the above-mentioned manufacturing method, an all-solid-state battery can be obtained.
[0142] The all-solid-state battery preferably has a structure in which a positive electrode layer containing a positive electrode active material, a negative electrode layer containing a negative electrode active material, and a solid electrolyte layer formed between the positive electrode layer and the negative electrode layer are stacked.
[0143] The method for producing the above-mentioned multilayer ceramic capacitor includes a method comprising: printing a conductive paste on the inorganic fine particle dispersed sheet of the present invention and drying it to produce a dielectric sheet; and laminating the above-mentioned dielectric sheets.
[0144] The above-mentioned conductive paste contains conductive powder.
[0145] The material of the conductive powder is not particularly limited as long as it is a conductive material, and examples thereof include nickel, palladium, platinum, gold, silver, copper, and alloys thereof. These conductive powders may be used alone or in combination of two or more.
[0146] The method for printing the conductive paste is not particularly limited, and examples thereof include screen printing, die coating printing, offset printing, gravure printing, and inkjet printing.
[0147] In the method for producing the above-mentioned multilayer ceramic capacitor, the dielectric sheets on which the above-mentioned conductive paste is printed are stacked, thereby obtaining a multilayer ceramic capacitor.
[0148] Effects of the Invention
[0149] According to the present invention, an inorganic particle dispersion slurry composition can be provided which has excellent low-temperature decomposition properties, can perform degreasing of perovskite-type inorganic materials below the Curie point, can suppress the degradation of magnetic force and piezoelectric properties of perovskite-type inorganic materials, and has excellent printability. In addition, a method for producing an inorganic particle dispersion sheet using the inorganic particle dispersion slurry composition can be provided. DETAILED DESCRIPTION
[0150] Hereinafter, the present invention will be described in more detail with reference to Examples, but the present invention is not limited to these Examples.
[0151] (Production Example 1)
[0152] A 2L separable flask equipped with a stirrer, a cooler, a thermometer, a hot water bath, and a nitrogen inlet was prepared. 60 parts by weight of isobutyl methacrylate (iBMA), 5 parts by weight of glycidyl methacrylate (GMA), and 30 parts by weight of n-butyl methacrylate (nBMA) were added to the 2L separable flask. Furthermore, 500 parts by weight of butyl acetate as an organic solvent was mixed to obtain a monomer mixed solution.
[0153] After bubbling the obtained monomer mixture with nitrogen for 20 minutes to remove dissolved oxygen, the inside of the separable flask was replaced with nitrogen, and the internal temperature was set to 80° C. while stirring, and a polymerization initiator solution diluted with butyl acetate was added. In addition, the polymerization initiator solution was added several times during the polymerization. It should be noted that dilauroyl peroxide was used as a polymerization initiator.
[0154] After 7 hours from the start of the polymerization, the mixture was cooled to room temperature to terminate the polymerization, thereby obtaining a composition containing a (meth)acrylic resin.
[0155] 5 parts by weight of polypropylene glycol (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd., propylene glycol segment length 1500) as a block segment and 2 parts by weight of 0.01N hydrochloric acid were added to the resin composition and reacted at 80°C for 2 hours. The remaining polypropylene glycol was evaluated by GPC and FTIR, and it was found that almost all of it was imparted to the (meth) acrylic resin in the form of a graft chain. Thus, a (meth) acrylic resin (A) having a polypropylene glycol block segment as a graft chain was obtained.
[0156] The obtained (meth)acrylic resin (A) was dried in an oven and dissolved in THF so as to have a resin concentration of 0.1 wt %. The molecular weight in terms of polystyrene was measured by GPC using SHODEX LF-804 as a column. The number average molecular weight was 30,000 and the weight average molecular weight was 60,000.
[0157] Separately, the dried (meth)acrylic resin (A) is saponified with an aqueous sodium hydroxide solution to hydrolyze the ester chain. The acrylic resin is dissolved in water, and an oil droplet-like component is separated.
[0158] The separated oil droplet-like component was dried and weighed, and the content of the block segment as a graft chain relative to the whole (meth)acrylic resin (A) was calculated by the following formula and found to be 10% by weight.
[0159] In addition, the molecular weight of the oil droplet-like component was confirmed by GPC, and the number average molecular weight was confirmed to be 1500. In addition, the number average molecular weight of the (meth)acrylic resin (A) after saponification was measured and calculated, and the result was that when the average length of the main chain was set to 100, the average length of the polypropylene glycol block segment as the graft chain was 5.
[0160] Furthermore, the ratio of the iBMA segment was confirmed by thermal decomposition GC-MS and found to be 60% by weight.
[0161] In Table 1, the graft chain content indicates the weight ratio of the structural unit having the graft chain in the (meth)acrylic resin (A), and the graft chain composition ratio indicates the weight ratio of only the graft chain portion excluding the main chain portion in the (meth)acrylic resin (A).
[0162] (Production Example 2)
[0163] Prepare a 2L separable flask equipped with a stirrer, a cooler, a thermometer, a hot water bath, and a nitrogen inlet. Add 5 parts by weight of maleic anhydride, 10 parts by weight of polypropylene glycol (propylene glycol segment length 230), and 40 parts by weight of ethyl carbitol acetate (boiling point 217°C) as a solvent to the 2L separable flask, and stir at 150°C for 2 hours under a nitrogen atmosphere to react maleic anhydride with polypropylene glycol. Further, add 60 parts by weight of iBMA and 25 parts by weight of methyl methacrylate (MMA). Further, add 700 parts by weight of ethyl carbitol acetate as an organic solvent and mix to obtain a monomer mixture. While adjusting the liquid temperature to 80°C, add the polymerization initiator in several portions to terminate the polymerization.
[0164] The number average molecular weight was 10,000 and the weight average molecular weight was 20,000 as measured by GPC in the same manner.
[0165] Furthermore, the remaining polypropylene glycol was evaluated by GC-MS, and it was found that almost all of it was imparted to the (meth)acrylic resin in the form of graft chains. Thus, a (meth)acrylic resin (A) having a polypropylene glycol block segment as a graft chain was obtained.
[0166] (Production Example 3)
[0167] A 2L separable flask equipped with a stirrer, a cooler, a thermometer, a hot water bath, and a nitrogen inlet was prepared. 4.6 parts by weight of 2-methacryloyloxyethyl isocyanate (Karenz MOI manufactured by Showa Denko K.K.) and 5.4 parts by weight of polytetramethylene ether glycol (PTMG250 manufactured by Mitsubishi Chemical Corporation) were added to another flask, and reacted at 60°C for 2 hours under a nitrogen atmosphere to obtain a methacrylic monomer having a polytetramethylene ether glycol chain.
[0168] 10 parts by weight of the obtained methacrylic acid monomer was transferred to a 2 L separable flask, and 70 parts by weight of iBMA, 20 parts by weight of 2-ethylhexyl methacrylate (2EHMA), and 20 parts by weight of hexyl acetate (boiling point 170° C.) as an organic solvent were added, and a polymerization initiator was added in multiple portions at 80° C. under a nitrogen atmosphere to carry out polymerization, thereby obtaining a (meth)acrylic resin (A) having a polytetramethylene ether glycol block segment.
[0169] The number average molecular weight was 200,000 and the weight average molecular weight was 400,000 as measured by GPC in the same manner.
[0170] (Production Example 4)
[0171] A 100 mL separable flask was equipped with a Wittmer fractionating tube, an L-type connecting tube, and a Dimroth cooling tube, 20 parts by weight of methacrylic acid (MAc) and 200 parts by weight of polytetramethylene ether glycol (molecular weight 1000) were mixed, and the mixture was reacted at 120°C for 1 hour while reducing the pressure to -0.1 MPa with a vacuum pump, and the reaction solution was diluted with chloroform, and unreacted MAc was removed using an LC column. The chloroform was evaporated with an air pump to obtain a (meth) acrylic resin having a polytetramethylene ether glycol block segment.
[0172] In a 2 L separable flask equipped with a stirrer, a cooler, a thermometer, a hot water bath and a nitrogen inlet, 20 parts by weight of the obtained (meth)acrylic resin, 50 parts by weight of iBMA, 20 parts by weight of ethyl methacrylate (EMA), 10 parts by weight of 2EHMA and 400 parts by weight of terpineol as an organic solvent were added, and a polymerization initiator was added in multiple portions at 80° C. under a nitrogen atmosphere to carry out polymerization, thereby obtaining a (meth)acrylic resin (A) having a polytetramethylene ether glycol block segment.
[0173] The number average molecular weight was 20,000 and the weight average molecular weight was 40,000 as measured by GPC in the same manner.
[0174] (Production Example 5)
[0175] A 2L separable flask equipped with a stirrer, a cooler, a thermometer, a hot water bath, and a nitrogen inlet was prepared. 40 parts by weight of propylene glycol monomethacrylate (PMA), 40 parts by weight of iBMA, and 20 parts by weight of nBMA were added to the 2L separable flask. Furthermore, 100 parts by weight of butyl acetate as an organic solvent was added and mixed to obtain a monomer mixed solution.
[0176] After nitrogen was bubbled through the obtained monomer mixture for 20 minutes to remove dissolved oxygen, the interior of the separable flask was replaced with nitrogen, and a polymerization initiator solution diluted with butyl acetate was added while stirring at an internal temperature of 80° C. The polymerization initiator solution was added several times during the polymerization.
[0177] After 7 hours from the start of the polymerization, the mixture was cooled to room temperature to terminate the polymerization. Thus, a (meth)acrylic resin (A) having an oxypropylene group was obtained.
[0178] The number average molecular weight was 100,000 and the weight average molecular weight was 200,000 as measured by GPC in the same manner.
[0179] (Production Example 6)
[0180] A 2L separable flask equipped with a stirrer, a cooler, a thermometer, a hot water bath, and a nitrogen inlet was prepared. 10 parts by weight of stearyl methacrylate (SMA), 80 parts by weight of iBMA, and 10 parts by weight of MMA as monomers having a long-chain ester substituent were added to the 2L separable flask. Furthermore, 90 parts by weight of ethyl carbitol acetate (boiling point 217° C.) was added as an organic solvent and mixed to obtain a monomer mixed solution.
[0181] While adjusting the obtained monomer mixed liquid to 80° C., a polymerization initiator was added in multiple portions to complete the polymerization, thereby obtaining a (meth)acrylic resin (A) having a stearyl group.
[0182] The number average molecular weight was 100,000 and the weight average molecular weight was 200,000 as measured by GPC in the same manner.
[0183] (Production Example 7)
[0184] A 2L separable flask equipped with a stirrer, a cooler, a thermometer, a hot water bath, and a nitrogen inlet was prepared. 4 parts by weight of polyethylene glycol monomethacrylate, 70 parts by weight of iBMA, and 26 parts by weight of 2EHMA as a monomer having a polyethylene glycol block were added to the 2L separable flask. Furthermore, 600 parts by weight of hexyl acetate (boiling point 170° C.) as an organic solvent was added and mixed to obtain a monomer mixed solution.
[0185] While adjusting the obtained monomer mixed liquid to 80° C., a polymerization initiator was added in multiple portions to complete the polymerization, thereby obtaining a (meth)acrylic resin (A) having a polyethylene glycol block segment.
[0186] The number average molecular weight was 20,000 and the weight average molecular weight was 40,000 as measured by GPC in the same manner.
[0187] (Production Example 8)
[0188] A 2L separable flask equipped with a stirrer, a cooler, a thermometer, a hot water bath, and a nitrogen inlet was prepared. 20 parts by weight of butanediol monomethacrylate, 40 parts by weight of iBMA, and 40 parts by weight of EMA as a monomer having a tetramethylene structure in an ester substituent were added to the 2L separable flask. Furthermore, 200 parts by weight of hexyl acetate (boiling point 170° C.) as an organic solvent was added and mixed to obtain a monomer mixed solution.
[0189] While adjusting the obtained monomer mixed liquid to 80° C., a polymerization initiator was added in multiple portions to complete the polymerization, thereby obtaining a (meth)acrylic resin (A) having an oxybutylene group.
[0190] The number average molecular weight was 40,000 and the weight average molecular weight was 80,000 as measured by GPC in the same manner.
[0191] (Examples 1 to 8, Comparative Examples 1 to 4)
[0192] (1) Preparation of Inorganic Microparticle Dispersion Slurry Composition
[0193] The (meth)acrylic resin (A), inorganic fine particles having a perovskite structure (B), and an organic solvent (C) shown in Table 1 were mixed to have the formulation shown in Table 1 and kneaded with a high-speed stirrer to obtain an inorganic fine particle dispersed slurry composition.
[0194] (2) Preparation of inorganic particle dispersion sheets
[0195] The obtained inorganic microparticle dispersion slurry composition was coated on a support film (width 400 mm, length 30 m, thickness 38 μm) comprising polyethylene terephthalate (PET) that had been previously subjected to demolding treatment using a blade coater, and the formed coating was dried at 100° C. for 10 minutes to remove the solvent, thereby forming an inorganic microparticle dispersion sheet with a thickness of 50 μm on the support film.
[0196] The support film was peeled off, and the inorganic fine particle dispersed sheet was laminated thereon to prepare a sheet having a thickness of 500 μm.
[0197] (3) Preparation of Inorganic Sintered Body
[0198] The obtained sheet was placed on a ceramic dish and heated in an electric furnace at 300°C for 10 hours to degrease the binder. After curing until it reaches room temperature, it was taken out of the oven and pressed in a magnetic field pressing device at a magnetic field of 10KOe and 10MPas to obtain a magnetically oriented inorganic sintered body.
[0199] [Table 1]
[0200]
[0201] <Evaluation>
[0202] The inorganic fine particle-dispersed slurry compositions and inorganic sintered bodies obtained in Examples and Comparative Examples were evaluated as follows.
[0203] (1) Sheet printing properties
[0204] In "(2) Preparation of Inorganic Fine Particle Dispersed Sheet", the coating film before drying was visually observed, and the sheet printability was evaluated based on the following criteria.
[0205] ○: The surface is smooth and glossy, which is a good condition.
[0206] △: Although it can be applied, the surface is not smooth.
[0207] ×: There are wrinkles and scratches, and the coating cannot be applied evenly.
[0208] (2) Degreasing properties
[0209] The amount of residual carbon in the obtained inorganic sintered body was confirmed using a carbon-sulfur analyzer manufactured by Horiba, Ltd., and the degreasing property (low-temperature decomposability) was evaluated based on the following criteria.
[0210] It can be said that the less the residual carbon is, the better the low-temperature decomposition property is.
[0211] ○: Residual carbon is 50 ppm or less.
[0212] △: Residual carbon is greater than 50 ppm and less than 100 ppm.
[0213] ×: The residual carbon is 100 ppm or more.
[0214] (3) Crystal analysis
[0215] The obtained inorganic sintered body was examined for the state of crystal formation using CuKα rays using a wide-angle X-ray diffraction apparatus manufactured by Rigaku Corporation, and the crystal formability was evaluated based on the following criteria.
[0216] If the crystal formability is excellent, performance equivalent to the theoretical value can be expected.
[0217] ◎: A strong diffraction peak was confirmed near 2θ=30°, and there was no small scattering up to 40°.
[0218] ○: A strong diffraction peak can be confirmed near 2θ=30°, and there is a small scattering between 30° and 40°.
[0219] △: The diffraction peak is split into two at around 2θ=30°.
[0220] ×: The diffraction peak near 2θ=30° is split into two, and strong scattering occurs between 30° and 40°.
[0221] (4) Sintered body characteristics
[0222] The obtained inorganic sintered body was measured for magnetic force using an AC magnetic susceptibility measuring device (XacQuan, Toyo Institute). In addition, the piezoelectric properties were confirmed using a ferroelectric evaluation system (FCE10, TOYO Corporation). In addition, the inorganic fine particles having a perovskite structure used in the examples and comparative examples were compacted without using a binder to prepare a sample, and the magnetic force and piezoelectric properties were similarly confirmed.
[0223] The degree of deterioration of the magnetic force or piezoelectric properties of the inorganic sintered body was confirmed with respect to the magnetic force or piezoelectric properties of the compacted sample, and the sintered body properties were evaluated based on the following criteria.
[0224] ◎: The degree of deterioration of magnetic force or piezoelectric characteristics is less than 10%.
[0225] ○: The degree of deterioration of magnetic force or piezoelectric characteristics is 10% or more and less than 20%.
[0226] △: The degree of deterioration of magnetic force or piezoelectric characteristics is 20% or more and less than 30%.
[0227] ×: The degree of deterioration of magnetic force or piezoelectric characteristics is 30% or more.
[0228] [Table 2]
[0229]
[0230] Excellent properties were confirmed in all evaluations for Examples 1 to 8. In particular, Examples 1, 2, 5, and 6, in which the average length of the block segments was 2 to 5 relative to the average length of the main chain, achieved very good crystal structures with little deterioration in magnetic or piezoelectric properties.
[0231] On the other hand, the inorganic sintered bodies obtained in Comparative Examples 1 to 4 had a large amount of residual carbon, a complex crystal structure, and significantly deteriorated magnetic and piezoelectric properties.
[0232] Industrial Applicability
[0233] According to the present invention, an inorganic particle dispersion slurry composition can be provided which has excellent low-temperature decomposition properties, can perform degreasing of perovskite-type inorganic materials below the Curie point, can suppress the degradation of magnetic force and piezoelectric properties of perovskite-type inorganic materials, and has excellent printability. In addition, a method for producing an inorganic particle dispersion sheet using the inorganic particle dispersion slurry composition can be provided.
Claims
1. An inorganic fine particle dispersion slurry composition comprising a (meth)acrylic resin A, inorganic fine particles B and a solvent C, The inorganic particles B are three-element inorganic materials or four-element inorganic materials having a perovskite structure. The three-element inorganic material or the four-element inorganic material having a perovskite structure is Nd2Fe 14 B or PbZrTiO3, The (meth)acrylic resin A has at least one of a polypropylene glycol block segment and a polytetramethylene ether glycol block segment, The (meth)acrylic resin A has the polypropylene glycol block segment or the polytetramethylene ether glycol block segment in the graft chain, The (meth)acrylic resin A contains 50 wt % or more and 70 wt % or less of a segment derived from isobutyl methacrylate, In the inorganic fine particle dispersion slurry composition, the content of the (meth)acrylic resin A is greater than 5 wt % and less than 30 wt %, the content of the inorganic fine particles B is greater than 40 wt % and less than 90 wt %, and the content of the solvent C is greater than 10 wt % and less than 60 wt %.
2. The inorganic fine particle dispersion slurry composition according to claim 1, wherein The composition ratio of the polypropylene glycol block segment and the polytetramethylene ether glycol block segment in the (meth)acrylic resin A is 5% by weight or more and 20% by weight or less.
3. A method for producing an inorganic fine particle dispersion sheet, comprising: applying the inorganic fine particle dispersion slurry composition according to any one of claims 1 to 2 and drying the composition to obtain a sheet; and calcining the sheet at a temperature of 350°C or less.
Citation Information
Patent Citations
Magnet, membrane, laminate, motor, generator, and automobile
WO2021065254A1
Binder resin composition and inorgnaic fine particle-dispersed paste composition
CN101137712A
Inorganic microparticle-dispersed paste composition
CN102333818A